ISLAMIC LAW STUDY ON THE DISTRIBUTION OF INHERITANCE FOR WIVES WHO BEAR THE FAMILY'S ECONOMIC BURDEN IN DEMAK - Abshor, Ulil (UNISSULA Semarang, 2023)
In this study, researchers examined the division of inheritance rights of women who work, in the view of Islam, the religious law of Islam views women especially in the study of women standing as a wife is no longer a career woman herself, she has become the right of the husband is no longer the rights of the elderly , the wife's good nature to help it, once again not to meet the needs of the family. This is not apart from the fact that sociological factors experienced by the women, in this case the wife who entered the modern era is a lot of wives who work to help the family economy even provide for the continuity of the family . This sometimes makes ricuhnya division of inheritance that occurred in the county Demak. One alternative to this problem is to prove by further data and research related to the rights of a woman in this case working wives who bear the economic part of the next of kin in the family. Understanding the obstacles and barriers experienced by a wife who works and trying to provide for his family in the division of the estate is a part. The purpose of this thesis writing which help provide knowledge and insight is deeply concerning hasanah Mawaris law, in particular the division of inheritance law wife of obtaining one per four-piece if it does not have children yet, if left offspring wife's part is one-eight. Thus God governs in the Qur'an Surah an Nisa 'verse twelve. Islamic law division of inheritance has been very fair, especially women, Islam does not mengkastakan women, especially mothers. Mother called the prophet three times by the king of the Prophet Muhammad, far above the father. Therefore, although the wife gets one per eight if she's a mother, does not matter to him, because the mother still gets consecrated a son, whose value is far from one-fourth and one-eight inheritance. Especially in Islamic law recognize shirkah.Keywords: wife, solehah, law.